Evaluation of gypsum-chitosan as a biomaterial in dental pulp protection - Azeez Al-Ibrahim, Hasan Subhi (2015)
In dentistry, preservation of vital pulp tissue through pulp therapy is a challenging clinical approach. In the procedure of direct pulp capping, the exposure site is sealed by dental material to maintain the vitality of the pulp and induce reparative dentin formation. Several materials such as calcium hydroxide and mineral trioxide aggregate have been used and investigated for dental pulp capping with limitations. Thus, chitosan (CHT) and calcium sulfate (pure gypsum - Gyp) incorporated with bone morphogenetic protein 2 (BMP-2) were chosen in this study to exploit their advantages and develop a biomaterial with high biological and mechanical characteristics. Gyp is highly biocompatible, moldable and used as carrier of antibiotic. CHT is biocompatible, has antibacterial activity and enhances tissue growth. BMP-2 induces differentiation of pulp cells into odontoblasts and reparative dentin formation. The aims of this study were to prepare an experimental gypsum-based biomaterial and to study the effects of the biomaterial with several concentrations of CHT (10%, 5%, 2.5%, 1%, and 0% chitosan solution) on setting time (min), pH value, compressive strength (MPa), solubility (%), antibacterial activity against cariogenic bacteria, and the proliferative activity of SHED. In addition, BMP-2 was incorporated with Gyp-CHT and its effect was evaluated on alkaline phosphatase activity (ALP) of SHED. The adhesion and proliferation of SHED on the experimental biomaterial was also observed by scanning electron microscope (SEM). Commercial dental liner Dycal and Fuji IX were prepared according to manufacturer’s instructions and selective properties were evaluated for comparison purpose. For the experimental biomaterials the results of setting time were ranged between 4.1 and 6.6 min which is considered acceptable for clinical application. The pH values after 24 hours were ranged 5.7 and 6.4 which is suitable for application as pulp capping. The compressive strength increased with higher CHT concentration in the biomaterial which ranged between 2.63 and 5.83 MPa. The solubility rate decreased with CHT incorporation compared to that without CHT except for Gyp-CHT 10% which showed the highest solubility. The experimental biomaterial showed potent antibacterial activity against S. mutans and S. sobrinus, which was more evident with greater CHT concentration and comparable with other lining materials. The biomaterial showed good cell compatibility to SHED in both direct and indirect MTS tests. The biomaterial tended to increase the release of ALP outside the cells. The experimental biomaterial induced the ALP activity of SHED with higher activity in biomaterial incorporated with BMP-2. SEM observations showed that the seeded SHED were apparently healthy, well adhered and were spread on the surface through proliferative activity. The in vitro results of this study suggest that the physical and mechanical properties of gypsum based chitosan biomaterials were acceptable in relation of pulp capping biomaterials. The ALP activity of SHED which is an indicator of mineralization was significantly higher in Gyp-CHT-BMP-2 biomaterials compared to Dycal. Antibacterial properties of experimental biomaterials were found comparable with the commercial materials. Thus, the crystalline gypsum impregnated with CHT and BMP-2 organic matrices may have the potential for application in vital pulp therapy.